Registro de los Derechos Humanos de Estados Unidos en 2012 ([China Intercontinental Press], 2013)
This book records the serious human rights problems in the U.S. in 2012, including the life and personal safety, civil and political rights, economic and social rights, racial discrimination, women and children's rights and U.S. violations of human rights against other countrys.